Anténor Firmin : haitian pioneer of anthropology. - Fluehr-Lobban, Carolyn (American Antropological Association, 2000)
Anténor Firmin published De I'Égalité des Races Humaines in 1885 in Paris as a response both to Arthur de Gobineau's racist tome L'lnégalité des Races (1853-55) and to the racialist anthropology of the nineteenth century. This pioneering work of anthropology has been translated for the first time into English by Assclin Charles as The Equality of the Human Races (Firmin [1885]2000). In 662 pages of the original text, Firmin systematically critiqued the anthropometry and craniometry that dominated the anthropology of his day, while he envisioned a broad, synthetic discipline that would follow once this narrow approach to the study of man was abandoned. He challenged virtually every extant racial myth and laid a basis for the understanding of human variation as adaptation to climate and environment. Contrary to the polygenist doctrines of the infertility of interracial matings, Firmin extolled the value of racial mixture, especially in the vigorous New World hybrid populations. He developed a critical view of racial classifications and of race that foreshadowed much later social constructions of race. In the book he also articulated early Pan-Africanist ideas as well as an analytical framework for what would become postcolonial studies.\\The Equality of the Human Races is a text that lies historically at the foundations of the birth of the discipline of anthropology, yet it is unknown to the field. It is a pioneering work in critical anthropology that awaits recognition 115 years after it was first published